Объяснение:
=3(x+∆x)² + 1 - (3x² +1 )=
=3x² + 6x∆x + 3∆x² +1 - 3x² - 1=
=6x∆x + 3∆x²
=(6x∆x+3∆x²) / ∆x=
=6x + 3∆x =
=[так как ∆х→0, то и 3∆х→0]=
=6х + 0=
=6х
=1/(x+∆x) - 1/x = (x - (x+∆x)) / (x+∆x)*x =
= (x - x - ∆x)) / (x+∆x)*x =
= (-∆x) / (x+∆x)*x
=((-∆x) / (x+∆x)*x ) / ∆x=
= - 1 / (x+∆x)*x =
=[так как ∆х→0, то х+∆х→х]=
= -1 / х*х=
= -1/х²
y'=-sin(x) (смотри прикрепленное изображение)
Объяснение:
f(x)=3x²+1∆x→0,∆y=y(x+∆x) - y(x)==3(x+∆x)² + 1 - (3x² +1 )=
=3x² + 6x∆x + 3∆x² +1 - 3x² - 1=
=6x∆x + 3∆x²
y'=∆y/∆x ==(6x∆x+3∆x²) / ∆x=
=6x + 3∆x =
=[так как ∆х→0, то и 3∆х→0]=
=6х + 0=
=6х
f(x)=1/x∆x→0,∆y=y(x+∆x)-y(x)==1/(x+∆x) - 1/x = (x - (x+∆x)) / (x+∆x)*x =
= (x - x - ∆x)) / (x+∆x)*x =
= (-∆x) / (x+∆x)*x
y'=∆y/∆x ==((-∆x) / (x+∆x)*x ) / ∆x=
= - 1 / (x+∆x)*x =
=[так как ∆х→0, то х+∆х→х]=
= -1 / х*х=
= -1/х²
f(x)=cos(x)y'=-sin(x) (смотри прикрепленное изображение)